A STUDY OF MEDICAL FACILITIES PROFIVDED BY PUNJAB EMPLOYEES SOCIAL SECRUITY INSTITUTIONS TO THE LABOURERS IN THE FAISALABAD CITY - M. I. Zafar; S. R. S. Abbasi; Z. Batool; I. Shahid (Journal of Animal and Plant Sciences, 2008)
Health is very important for improving human efficiency and out put. It is extremely essential for those who are involved in laborious jobs in factories producing consumer goods and engaged in large industrial units. Increasing workers protests about lack or limited availability of health services, frequent media reporting and discussion at professional forums have raised concerns about this important social issue in society. Faisalabad is an important industrial city of Pakistan with a major part of its labour force working in various types of industries. Health services to these workers and their dependent family members are important aspects of their lives as well as for raising production at these industries. In view of importance of this social issue, a micro level study was conducted to explore the extent of health services extended by the Punjab Employees Social Security Institution (PESSI) to labourers working in industrial units located in Faisalabad city. Data was collected through field survey from randomly selected four textile industries. A random sample of 200 respondents revealed that employers provide medical facility in case of emergency. The medical facilities provided by PESSI to workers and their dependent family members were inadequate. A reasonable majority also indicated that PESSI gave daily allowance only to secured workers during their hospitalization.
Keywords: Factory workers; health services; social security; satisfaction level